The consultation of the public in mobility projects: An overview of the municipal participation landscape in Germany - Mark, Laura; Katharina Holec,; Tobias Escher, (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
Municipalities as key players in the transport transition, local authorities are increasingly using consultative public participation in planning. So far, however, it is unclear to what extent they use participatory processes in mobility-related planning and how these are organised. This paper closes this knowledge gap based on an analysis of the consultative, discursive participation processes for mobility-related planning in German cities since 2015. 180 cities and 350 procedures were analysed to determine to what extent an what characteristics in German municipalities use consultative, discursive participation procedures in mobility-related planning and what possible influence of the respective context can be derived from this. The study analyses ‘participation-oriented’ cities with guidelines for citizen participation, which were compared to a random selection of ‘typical’ municipalities in North Rhine-Westphalia, Baden-Württemberg and Saxony as well as the three German city states. It is clear that discursive consultations are carried out regularly, in particular in municipalities with guidelines and larger cities. Yet in most cities such processes are still the exception. Worth criticizing is that the formats used can usually reach only certain groups of the population and that for a significant proportion of the processes examined no information on the results of participation can be found. As a result, the potential of discursive citizen participation in addressing the municipal transport transition have not yet been sufficiently utilised.
Keywords: Mobility transition; Citizen participation; Municipalities; Germany; Consultation